Bystander Intervention in Coercive Control: Do Ethnic Identity and Acceptance of Coercive Control Influence Willingness to Intervene? - Reynolds, Hannah (Journal of interpersonal violence, 2024)
Previous intimate partner violence research and social psychological theory have highlighted that ethnicity and level of harm are both factors that have the potential to influence bystander willingness to intervene in, as well as the acceptance of intimate partner violence between couples. Little research has been conducted on the general willingness of bystanders to intervene in, or the level of acceptance of coercive control. This is the first study to explore whether the likelihood of bystander willingness to intervene is influenced by participant gender, the ethnicity of the couple involved in a hypothetical scenario of coercive control, and by differing levels of abusive behavior. In this study, we also explored the influence of participants’ acceptance of coercive control. A semi-experimental design was used, utilizing an online community sample sourced through social media of 346 adult participants across Australia. The participants were randomly allocated to read a fictional coercive control scenario detailing either low or high harm instances of coercive control. Within the online survey the ethnicity of the couple was manipulated with participants’ randomly allocated to read a scenario about a couple with the same ethnicity as them (Australian of British or European descent) or a couple with Indian Australian ethnicity. The results showed the participants were significantly more willing to intervene in the coercive control scenario when the couple shared the same ethnicity as them. In response to the low harm scenarios, participants were significantly more accepting of coercive control if the couple were Indian Australian. However, males responding to high harm scenarios were more accepting of coercive control if the couple shared the same ethnic identity as them. The implications from these findings for theory and future bystander intervention programs are discussed.